Discovery and structural studies of histone demethylases - Peng, Longfei; Li, Xinze; Yang, Hao; Chen, Haonan; Yang, Yue; Peng, Shunfeng (Frontiers in Epigenetics and Epigenomics, 2025)
The discovery and structural elucidation of histone demethylases represent a groundbreaking advancement in the field of epigenetics. Histone methylation, a critical chromatin modification, was long regarded as irreversible until the identification of histone demethylases overturned this paradigm. In 2004, the discovery of the first histone demethylase, LSD1 (Lysine-Specific Demethylase 1), unveiled the dynamic regulatory mechanisms governing methylation modifications. Subsequent identification of the JmjC domain-containing demethylase family further expanded the diversity and functional repertoire of these enzymes. Structural biology studies have revealed the molecular mechanisms by which these enzymes remove methyl groups via oxidation or hydroxylation reactions, providing key insights into their substrate specificity and catalytic processes. This article will provide a concise overview of the discovery history, fundamental structures, and functional mechanisms of histone demethylases, summarize research progress on identified histone demethylases, and offer novel insights and offer novel insights and suggestions for fundamental research on sites where demethylases remain undiscovered.